Case Report: Association between cyclic neutropenia and SRP54 deficiency - Erdős, Melinda; Boyarchuk, Oksana; Maródi, László (Frontiers in Immunology, 2022)
Autosomal dominant mutations in the signal recognition particle (SRP) 54 gene were recently described in patients with severe congenital neutropenia (SCN). SRP54 deficiency cause a chronic and profound neutropenia with maturation arrest at the promyelocyte stage, occurring in the first months of life. Nearly all reported patients with SRP54 mutations had neutropenia without a cyclic pattern and showed a poor or no response to granulocyte colony-stimulating factor (G-CSF) therapy. We report here an 11-year-old female patient with cyclic neutropenia and recurrent heterozygous p.T117del (c.349_351del) in-frame deletion mutation in SRP54, who showed remarkable therapeutic response to G-CSF treatment. The diagnosis of cyclic pattern of neutropenia was established by acceptable standards. ELANE gene mutation was excluded by using various genetic approaches. The patient described here also had dolichocolon which has not been described before in association with SCN.